The Relationship of Ephesians and Colossians - Coutts, John (New Testament studies, 1958)
In a previous number of New Testament Studies (II(1957), 115-27), I argued that behind Ephesians i. 3-14 and I Peter i. 3-12 lie forms of liturgical prayer; that Ephesians as a whole might well be a Baptismal Encyclical; and that if this were so, the question of the priority of Colossians might have to be reconisdered.